Humanitarian aid in precarious camps reflexes on the interpersonal relationships of refugees - de Barros Souza, Beatriz; Garcia, Agnaldo (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2024)
Currently, many of the over 35 million people who are recognized as refugees by some — usually underdeveloped or developing — countries live in precarious camps, where diverse humanitarian aid actions predominate, such as those for “mental health and psychosocial support” (MHPSS). This narrative literature review considers the effects of MHPSS on the refugees’ interpersonal relationships within the camps, discussed in light of the theoretical contributions of both Robert Hinde and Axel Honneth to the Social Sciences. It is hoped that the conceptual tools herein provided can guide a thematic analysis of how humanitarian aid operates, as well as its main challenges, within precarious refugee camps.